Antibody anti-H5N1 detection in poultry farmers and workers in poultry collection facilities in Indonesia, 2007 (Medical Journal of Indonesia, 2010)
Aim Between July 2005 and May 2008, Indonesia reported 133 H5N1 confirmed human cases with a case fatality proportion of 81%. Fifty-four percent of cases had a history of direct contact with poultry (chickens). Therefore, it is important to define the detection of antibody of H5N1 among people who have intensive contact with poultry have been exposed to H5N1 viruses. Methods We collected sera from healthy poultry-collecting-facility (PCF) workers in Jakarta and healthy poultry-farmers in Sukabumi which have close contact with poultry. Anti-H5N1 antibodies were tested with modified Haemagglutination Inhibition (HI) assay using A/Ck/Banten/05-1116/05(H5N1) antigen and with Neutralization (NT) assay using A/H5N1/Indo/05/IBCDC-RG virus. Results Among the 216 PCF worker sera and the 495 poultry-farmer sera that we collected, we found that all poultry-farmers were seronegative and one percent of poultry-collecting-facilities workers were seropositive by both HI and 1% by NT assays. Conclusions This study detected asymptomatic H5N1 virus infection among poultry workers in PCFs with intensive contact with various types of different poultry who had different titers of antibody, but no antibodies were detected among poultry farmers. (Med J Indones 2010; 19:124-9)